Microwaving Blood as a Non‐Destructive Technique for Haemoglobin Measurements on Microlitre Samples. Issue 4 (4th September 2013) - Basey‐Fisher, Toby H.; Guerra, Nadia; Triulzi, Chiara; Gregory, Andrew; Hanham, Stephen M.; Stevens, Molly M.; Maier, Stefan A.; Klein, Norbert
<x xml:space="preserve">Abstract</x> The non‐destructive ex vivo determination of haemoglobin (Hgb) concentration offers the capability to conduct multiple red blood cell haematological measurements on a single sample, an advantage that current optical techniques are unable to offer. Here, a microwave method and device for the accurate and non‐destructive determination of Hgb concentration in microlitre blood samples are described. Using broadband microwave spectroscopy, a relationship is established between the dielectric properties of murine blood and Hgb concentration that is utilized to create a technique for the determination of Hgb concentration. Subsequently, a microwave dielectric resonator‐microfluidic system is implemented in the analysis of 52 murine samples with microlitre volumes and Hgb concentrations ranging from 0 to 17 g dL−1. Using the characterized relationship, independent and minimally invasive Hgb measurements are made on nine healthy mice as well as seven with mutations in the Adenomatous polyposis coli (APC) gene that leads to colorectal cancer and consequently anaemia.